Technical Note: Improving proton stopping power ratio determination for a deformable silicone‐based 3D dosimeter using dual energy CT. Issue 6 (10th May 2016) - Taasti, Vicki Trier; Høye, Ellen Marie; Hansen, David Christoffer; Muren, Ludvig Paul; Thygesen, Jesper; Skyt, Peter Sandegaard; Balling, Peter; Bassler, Niels; Grau, Cai; Mierzwińska, Gabriela; Rydygier, Marzena; Swakoń, Jan; et al.
Abstract : Purpose: The aim of this study was to investigate whether the stopping power ratio (SPR) of a deformable, silicone‐based 3D dosimeter could be determined more accurately using dual energy (DE) CT compared to using conventional methods based on single energy (SE) CT. The use of SECT combined with the stoichiometric calibration method was therefore compared to DECT‐based determination. Methods: The SPR of the dosimeter was estimated based on its Hounsfield units (HUs) in both a SECT image and a DECT image set. The stoichiometric calibration method was used for converting the HU in the SECT image to a SPR value for the dosimeter while two published SPR calibration methods for dual energy were applied on the DECT images. Finally, the SPR of the dosimeter was measured in a 60 MeV proton by quantifying the range difference with and without the dosimeter in the beam path. Results: The SPR determined from SECT and the stoichiometric method was 1.10, compared to 1.01 with both DECT calibration methods. The measured SPR for the dosimeter material was 0.97. Conclusions: The SPR of the dosimeter was overestimated by 13% using the stoichiometric method and by 3% when using DECT. If the stoichiometric method should be applied for the dosimeter, the HU of the dosimeter must be manually changed in the treatment planning system in order to give a correct SPR estimate. Using a wrong SPR value will cause differences between the calculated and the delivered treatment plans.